Benign gastric ulceration in a health district: incidence and presentation. Issue 718 (August 1985) - Glynn, M. J.; Kane, S. P.
Abstract : In a survey of benign gastric ulceration conducted in the Hounslow Health District from 1981 to 1982, there was an annual incidence for this condition of 43.6 per 100, 000 of the population older than 14 y, with a male:female ratio of 0.9:1. This incidence is comparable to that found in other surveys over the last 30 y, but the male:female ratio is lower than in the past. This reduction is accounted for by a rise in the peak age incidence for gastric ulcer, particularly in women, and a greater proportion of the total population in this higher age group being women. In spite of a large local Asian population, no gastric ulcers occurred in this ethnic group. Thirty-eight per cent of the patients presented with acute bleeding, and 44% of these bleeders gave a history of previous ingestion of non-steroidal anti-inflammatory drugs compared with only 14% of the non-bleeding group (P less than 0.015).